Zn(ii)-metallo-photoantibiotics: experimental and computational approach identifying a therapeutic role for antibacterial and antibiofilm applications - Kushwaha, Rajesh; Kumari, Sangeeta; Mishra, Arya; Upadhyay, Anjali; Rai, Archana; Nayak, Malay; Mukherjee, Sudip; Banerjee, Samya (Chemical Communications, 2025)
The antibacterial profiles of curcumin-based novel Zn(ii)-metallo-photoantibiotics against E. coli and B. subtilis are reported. In silico studies indicated their ROS generation capacity and binding interaction with bacterial proteins. Therapeutic results indicated the advantages of these Zn(ii)-metallo-photoantibiotics in antibacterial photodynamic therapy.